Factors affecting the roles and functions of nursing managers in selected hospitals in Bandung and Jakarta, Indonesia - Ibrahim, Christina S.
This study had 2 objectives: 1) to determine the expectations of nurses, physicians, and clients on the roles and functions of nursing managers and 2) to identify the factors that affect these roles and functions. It sought to answer 4 questions about: 1) the roles and functions as observed and as expected by nurses, physicians and clients; 2) the differences between observed and expected roles and functions of the nursing managers and the differences in expectations by type of hospital and type of respondents; 3) relationship of professional, organizational, client, and personality factors to the expected roles and functions of nursing managers; and 4) the total relative effects of professional, organizational, client, and personality factors on these roles and functions. The hypotheses of the study are: 1. There are differences between the roles and functions of nursing managers as observed and expected, and across type of hospital and respondent. 2. Professional, organizational, client, and personality factors significantly affect the roles and functions of the nursing managers. 3. These 4 factors have differential effects on the expected roles and functions of the nursing managers. The expected roles and functions of the nursing managers are the dependent variables in this study. 4 groups of expected roles and functions were investigated: 1) general management roles and functions including analyzing problem, decision making, and communication; 2) sequential management roles and functions, including planning, organizing, staffing, directing and controlling; 3) leadership; and 4) modelling. Professional, organizational, client, and personality factors strongly affect all the expected roles and functions of the nursing managers except communication. Most of the roles and functions are positively affected by the independent variables. Client factors, however, tend to have negative effects particularly client income, education and occupation. Professional factors represented by professional beliefs of nurses appear to be the single most important and most consistent predictor of all the managerial functions. Client factors, specially client income, rank 2nd best predictor, affecting inversely all functions, while organizational factors represented by the hospital resources variable are the 3rd best predictor, consistently predicting the management functions of all levels of nursing managers. Based on the findings of the study a set of job description is recommended for the 3 levels of nursing managers. Further implications and recommendations for nursing service, education and research, hospital administration, and the Indonesian Nurses Association are also included.